The Depiction of Bullying in Selected Children’s Books - Titin Kartini (Morphosis: Journal of Literature, 2024)
This study analyzes the bullying represented in “The Depiction of Bullying in Selected Children’s Books”. This study applies the qualitative research method as the analysis is presented in text and pictures. To guide this study, the writer used the perspective of Dan Olweus (1973) on bullying and its impact. This study examined bullying issues and their impact in First Fiction Supercow Volume II: The Bully by Danielle Bruckert, published in 2013, Second Fiction Giraffe is Left Out by Sue Graves published in September 2014, and Third Fiction Bully Bill by T. Albert, published in October 2015. The analyses clearly between bullying and its impact on children. The acts and attributes are categorized differently based on what is considered appropriate for children. By separating bullying and its impact into completely different categorizations through the appearances, traits, and behavior, the fiction books represented bullying act and their impact that happened daily in the children's school environment. This research scrutinized bullying based on the theory of bullying by Olweus that covers the experienced of bullying by the characters. Bullying can harm a person's self-esteem, friendships, life, and future. Characters that are bullied frequently suffer from despair, lifelong poor self-esteem, timidity, loneliness, physical diseases, and threats or attempts at self-harm. Bullying that is verbal, social, or relational can be as harmful as physical bullying. Keywords: bullying, fiction, children’s literature, impact of bullying, illustrative and narrative elements